Professional image of nurse and its determinants - Kojder, Ewelina; Zarzycka, Danuta (Nursing in the 21st Century, 2014)
PROFESSIONAL IMAGE OF NURSE AND ITS DETERMINANTSIntroduction. Professional image of nurses depends on many factors that determine perceiving nurses by public opinion. The image of this profession is created by beliefs, opinions, stereotypes, attitudes and also professional, personal, interpersonal characteristics attributed to nurses. Media has a significant role in building the opinions as well. The patients become a more and more demanding subject of care, which is associated with a great challenge for nurses, who want to care about their favorable professional image.Aim. This study is an attempt to analyze and compare the results of studying opinions about professional image of nurses and their determinants.Materials and methods. In the study, the method of literature analysis was used. The review is based on the data contained in Viamedia, GBL and Google Scholar. There were also used contents available in Polish and American web pages.Results. The image, which is the closest to society, is a nurse like “angel of goodness”. Everyone, despite the fact that it is not considered as attractive, holds this profession in high esteem. Determinants, which have the biggest influence on professional image of nurses, are personal culture and high quality of care. Small autonomy and low salary of nurses are the factors that have a negative influence on professional image of nurses.